ВАЖЛИВІСТЬ ВОКАЛЬНИХ ПОСТАВОК У ФОРМУВАННІ СПІВОЧИХ НАВИЧОК ДИТИНИ (Педагогіка вищої та середньої школи, 2006)
1п article importance vocal short-melodies in formation of singing ski Ils o f the child is considered; principles of selection of vocal exercises are allocated.